Peran Citra Merek dan Kualitas Layanan dalam Meningkatkan Keputusan Anggota terhadap Pembiayaan Produktif: (Studi Kasus BMT Al-Barokah Kaladawa Tegal) - Sakhuri Sakhuri (Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of brand image and service quality on members’ decisions to obtain productive financing at Baitul Maal wat Tamwil (BMT) Al-Barokah Kaladawa, Tegal. The research is motivated by the vital role of BMTs in providing sharia-compliant financing access for communities underserved by conventional financial institutions, and the need to strengthen brand image and service quality amidst increasing competition among Islamic microfinance institutions. This study employs a quantitative associative approach. Data were collected through questionnaires distributed to 100 active members of the BMT and analyzed using multiple linear regression with SPSS. The results indicate that brand image has a positive and significant effect on members’ decisions in choosing productive financing. Similarly, service quality shows a positive and significant influence on financing decisions. Simultaneously, both variables explain 60% of the variation in members’ financing decisions. These findings suggest that strengthening a sharia-based brand image and improving responsive, empathetic, and reliable service quality can enhance members’ decisions to use BMT’s financing products. This study contributes theoretically to the development of Islamic marketing management literature and provides practical implications for BMTs in formulating strategies to improve competitiveness and member loyalty.